(untitled) (One Health & Risk Management, 2021)
Introduction. Eating disorders are an important medical and social problem, remarkable potential for chronicity and onset in most cases at a young age. Causes of apparition of eating disorders are genetic factors, psychiatric disorders, anxiety disorders, society and professional goals. Eating disorders considerably impair physical health and disturb the homeostasis of body and systems. These irreversible changes in diet lead to physical, emotional and social consequences. The treatment of these food problems is difficult, complex and requires joint efforts. Material and methods. The search strategy was developed in the PubMed database, between October 2020 and April 2021. Search key words such as "eating disorders", "adolescents" were used. The filter for the date of publication has been set for the last 10 years. In total, 1265 accessible articles were researched, of which 93 Meta-Analysis, 21 Randomized Controlled Trial and 37 Systematic review were relevant. Most publications come from highly developed countries. Results. Adolescents are often exposed to harmful products such as tobacco, alcohol and drugs, face higher risks of violence and injuries from road traffic than in childhood, and may experience devastating mental health problems such as depression, anxiety, self-harm, substance abuse and video game addiction, as well as eating disorders and suicide. The most common eating disorders were: anorexia nervosa, bulimia nervosa and binge-eating. In USA, 18% of adolescents at the age of 16 already have at least one episode of eating disorder, Austria has the highest rate of prevalence of eating disorders in Europe at 1.55%. In Italy prevalence for anorexia nervosa of adolescents was 0.42%, for bulimia nervosa – 0.32% and for binge eating syndrome – 0.32%. Food avoidance is seen in almost 97% of children with restricted eating disorders, food preoccupation in over 80% and an extreme fear of "gaining weight" in over 70%. Bulimia nervosa affects both sexes and the average age of onset is about 12-14 years. The prevalence of bulimia nervosa is 0.9% among American adolescents. The adolescent population found higher prevalence in bulimia nervosa is from 1.1% in a 15-17 years old Italians to 1.2% in Sweden. The age of onset for binge-eating is in late adolescence, although estimates vary to early adulthood 17-20 years. Over 70% of individuals with eating disorders report comorbid disorders: anxiety disorders (>50%), mood disorders (>40%), self-harm (>20%), and substance use (>10%). There are more consequences of eating disorders, the most important are iron deficiency anemia, obesity (that includes other complications like metabolic syndrome; diabetes, arterial hypertension), dental caries, secondary amenorrhea in anorexia nervosa and the most important consequence is the death. Conclusions. Current trends in eating disorders highlight the increasing prevalence of eating disorders. In the treatment of eating disorders should be formed a multidisciplinary team with family doctors, teachers, psychologists and family.